Bone Collagen Turnover in Idiopathic Scoliosis Estimated from Total Hydroxyproline Excretion. Issue 250 (December 1971) - Zorab, P. A.; Clark, Stephanie; Cotrel, Y.; Harrison, Ailie
Abstract : The turnover of bone collagen is reflected by the 24-hour excretion of urinary total hydroxyproline. In idiopathic scoliosis there is an increase above normal in the turnover of bone collagen throughout adolescence. Spinal immobilization in plaster-of-Paris, spinal traction, and spinal fusion are all accompanied by increases in the turnover of bone collagen. It is suggested that estimation of the urinary total hydroxyproline excretion is useful in monitoring spinal changes during the treatment of children with idiopathic scoliosis and may reflect otherwise unsuspected changes in the bone collagen.